Caenorhabditis elegans sebagai Model Hewan Penelitian Biologi dan Biomedis - Susilowati, Rina Priastini; Santoso, Adit Widodo; Sabini, Jasmine Harumi (Jurnal MedScientiae, 2024)
Caenorhabditis elegans is a microscopic nematode, with a transparent body, short life span, self-fertilization ability. C. elegans is easy to be cultured and has been used as an animal model for molecular research, medicine, pharmacology, and toxicology. In addition, C. elegans was the first animal to have its genome completely sequenced and has played a major role in understanding apoptosis and RNA interference. The use of C. elegans as a biological model in environmental toxicology assessments has allowed for the determination of several endpoints. Some of these utilize effects on the biological functions of the nematode and others use molecular markers. Furthermore, C. elegans has enabled the assessment of neurotoxic effects for pesticides and heavy metals, since this nematode has a very well-defined nervous system. Overall, almost every known toxin has been tested in this animal model. In the near future, the knowledge available about the life cycle of C. elegans will allow for more studies on reproduction, transgenerational toxicity for newly developed chemicals and materials, and detailing the signaling pathways involved in the mechanisms of toxicity. C. elegans is an important animal model for research into the identification and understanding of the machinery of nuclear transport. This has helped elucidate biochemical pathways involved in diseases such as obesity, diabetes, and Alzheimer's disease. C. elegans is an excellent animal model for studying aging because of its short lifespan, susceptibility to oxidative stress, and similarity to the human aging process.